2019
DOI: 10.1038/s41598-019-48961-0
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii-induced host cellular cell cycle dysregulation is linked to chromosome missegregation and cytokinesis failure in primary endothelial host cells

Abstract: Toxoplasma gondii is a zoonotic and intracellular parasite with fast proliferating properties leading to rapid host cell lysis. T. gondii modulates its host cell on numerous functional levels. T. gondii was previously reported to influence host cellular cell cycle and to dampen host cell division. By using primary endothelial host cells, we show for the first time that T. gondii tachyzoite infections led to increased host cell prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(71 citation statements)
references
References 52 publications
7
62
2
Order By: Relevance
“…This finding contrasts with data on T. gondii infections which were reported either to dampen host cell proliferation in non-endothelial cell types (Brunet et al 2008;Molestina et al 2008;Kim et al 2016) or to trigger proliferation in the same endothelial cell type we used (Velásquez et al 2019). Accordingly, we could also not state an infection-driven increase of bi-or multi-nucleated host cells as previously reported for T. gondii infections (Velásquez et al 2019). In this respect, the combination of DRAQ5 staining with live cell 3D-holotomographic microscopy easily allowed nuclear phenotype estimation and nicely illustrated B. besnoiti development in BUVEC.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This finding contrasts with data on T. gondii infections which were reported either to dampen host cell proliferation in non-endothelial cell types (Brunet et al 2008;Molestina et al 2008;Kim et al 2016) or to trigger proliferation in the same endothelial cell type we used (Velásquez et al 2019). Accordingly, we could also not state an infection-driven increase of bi-or multi-nucleated host cells as previously reported for T. gondii infections (Velásquez et al 2019). In this respect, the combination of DRAQ5 staining with live cell 3D-holotomographic microscopy easily allowed nuclear phenotype estimation and nicely illustrated B. besnoiti development in BUVEC.…”
Section: Discussioncontrasting
confidence: 99%
“…Bars represent the median ± SD against the non-infected cells control. **** = p < 0.0001 recently published T. gondii data (Velásquez et al 2019), the current study was performed in a primary bovine endothelial cell type. Furthermore, by using a primary host cell type, false influences on host cellular cell cycle progression or cell division activities driven by cell immortalization or tumoral origin was avoided (Mondello and Chiodi 2013).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…S4C). These findings are consistent with potential induction of cell cycle arrest in U-I cells by injected effectors, as previously reported (3841).…”
Section: Resultssupporting
confidence: 93%
“…Using RPE and Müller cells, isolated from Lewis rats, Delair et al (2009) indicated that TNF-α and IFN-γ differentially restrict in vitro T. gondii infection, thus indicating that RMC are more susceptible to infection than RPE. Finally, it was recently described that T. gondii disrupts correct cytokinesis patterns and the formation of the mitotic spindle in bovine endothelial cells (Velásquez et al, 2019). It is known that changes in spindle structure, with or without cell cycle protein alterations, can lead to abnormal retinal and brain cortex development (Uzquiano et al, 2018), which could also explain how CT affects these processes.…”
Section: Congenital Toxoplasmosismentioning
confidence: 99%